Formação do leitor surdo na perspectiva dos multiletramentos: estratégias de ensino e aprendizagem - Xavier, Lóris Marta Matozo Soares (2024)
Linked to the Reading and Reader Training research line of the Graduate Program in Literature at the University of Passo Fundo (UPF), this study analyzes reading comprehension in the learning of Portuguese Language (L2) by Deaf individuals, in light of multiliteracies. As a result, this research is dedicated to the theme of the training of Deaf readers from the perspective of multiliteracies and explores the use of multimodal genres, such as cartoons and advertising and social propaganda, as pedagogical strategies for teaching reading to Deaf students. The choice of these multimodal genres is justified by their ability to integrate multiple modes of language, emphasizing visuality, which is crucial for Deaf individuals, since imagery resources evoke visual, gestural and spatial elements. The central question that guides this study is: how can multiliteracies, through multimodal genres and reading strategies, enhance the development of reading comprehension among Deaf individuals served by the Association of Deaf Parents and Friends of Passo Fundo (APAS), promoting greater autonomy and engagement in the learning process? To this end, the general objective is to verify the contributions of a teaching approach from the perspective of multiliteracies, supported by multimodal genres, such as cartoons and advertisements, as well as by the reading strategies proposed by Solé (1998), in the process of teaching and learning reading in the educational context of Deaf students, with an emphasis on the social practices of reading. To develop the general objective and address the research problem, the following specific objectives were defined: i) to characterize the distinct relationships between Libras and Portuguese as an additional language (L2) in the processing of reading; ii) to understand how multiliteracies can contribute to the development of the reading formation of Deaf students; iii) to carry out educational practices based on multimodal genres (cartoons and advertisements) linked to reading strategies; iv) to analyze teaching practices from the perspective of multiliteracies and the use of multimodal genres that favor the development of reading comprehension in L2. With this scope, the research is based on the theoretical references of authors such as Rojo (2012), Solé (1998), Quadros (2008), Kleiman (1995), among others. This qualitative and exploratory research investigates the reading development of deaf people, using bibliographical research and action research. Data collection took place over six meetings and five workshops at APAS, with the participation of five deaf people. The workshops focused on the use of multimodal genres, such as cartoons and advertisements, as pedagogical tools to improve reading comprehension, considering the predominance of visual and digital communication. The results of this research reveal that the practices reached reasonable levels, given that the participating students have a very limited vocabulary in Libras (L1), which made learning Portuguese (L2) difficult. In many instances, it was necessary to teach signs in Libras in addition to what was already planned for the work in L2. However, the analysis performed demonstrates that multimodal genres have great potential for teaching reading to deaf people, contributing to the development of skills aimed at reading comprehension.